Genetic Engineering and Biosecurity: An Analysis of Literature and Anticipated Future Developments - Alrawi, Mohaimen Oday Hazim; Aalhasan, Mohammed Najeeb Abdulmaged; Al-Daamy, Ammar Malik Kadhim (American Journal of Botany and Bioengineering, 2025)
The discovery of DNA as the fundamental material for heredity and biology has led to the development of various techniques for manipulating genetic material, allowing for the modification of organisms to benefit society and provide essential materials in the agricultural, industrial, and medical sectors. The emergence of CRISPR technology has further facilitated genetic modification, leading to significant advancements. However, these rapid developments in genetic engineering have raised concerns regarding the potential misuse of biotechnology for the production of biological weapons. Consequently, there has been a notable emphasis on developing effective detection methods for such weapons, culminating in the establishment of international agreements, such as the Geneva Convention, aimed at preventing the use and proliferation of biological weapons.